Industrial composting as a waste management method of polyester materials obtained from renewable sources - Sikorska, Wanda; Musioł, Marta; Rydz, Joanna; Kowalczuk, Marek; Adamus, Grażyna (Polimery, 2021)
This work presents a methodology for testing the biodegradation process of prototype products made of polylactide and its polymer compositions with polyhydroxyalkanoates under conditions of industrial composting. The samples were incubated in a composting pile, KNEER containers system or BIODEGMA system at the Segregation and Composting Station in Zabrze. The developed methodology allows the assessment of whether the tested materials and final products, with appropriate functional properties, are suitable for organic recycling.